Optimalisasi Model Project Based Learning terhadap Motivasi Belajar Mahasiswa Calon Guru Fisika Di Era New Normal - Aji Saputra; Saprudin Saprudin; Fatma Hamid; Nurdin Abdul Rahman (U-Teach: Journal Education of Young Physics Teacher, 2023)
Education is one of the sectors that has been affected by the Covid-19 pandemic. Currently we have entered the "New Normal" era, so it is very interesting to do more research on education. The purpose of this study was to explore student learning motivation in Computer Programming courses using the Project Based Learning model. This research involved 25 students of the Physics Education at Universitas Khairun. The instrument used for data collection was a Google Form-based questionnaire that had been validated with the Gregory Technique. The results showed that the average student learning motivation was high. Furthermore, to dig up more detailed information, interviews were conducted with several students. It should be noted that prior to the "New Normal" era, students studied online with all the limitations, and from the interview results, information was obtained that the project based learning model in the "New Normal" era helped learning activities